Silicon germanium materials & devices : a market & technology overview to 2006 - Szweda, Roy (Elsevier, 2002)
The first edition of Silicon Germanium Materials & Devices - A Market & Technology Overview to 2006 examines the development of the silicon germanium business over a six-year period 2001 to 2006. It analyses the trends in markets, technologies and industry structure and profiles all the major players. It is specifically aimed at users and manufacturers of substrates, epiwafers, equipment and devices. The analysis includes a competitive assessment of the market of silicon germanium vs. gallium arsenide, indium phosphide vs. other forms of silicon. Silicon Germanium Materials & Devices - A Market & Technology Overview to 2006 is designed to assist with business plans, R & D and manufacturing strategies. It will be an indispensable aid for managers responsible for business development, technology assessment and market research. The report examines the rapid development of silicon germanium from an R & D curiosity to production status. An extensive treatment from materials through processes to devices and applications it encapsulates the entire silicon germanium business of today and assesses future directions. For a PDF version of the report please call Tina Enright on +44 (0) 1865 843008 for price details.